Airway management in penetrating thoracic trauma - SARAÇOĞLU, AYTEN (My University, 2022)
© 2022 Via Medica. All rights reserved.Penetrating thoracic trauma accounts for 20-25% of all deaths due to trauma in the first four decades of life. About 33% of deaths from thoracic trauma occur due to penetrating trauma. In an autopsy study that enrolled 1178 trauma patients, 82% of the patients with tracheobronchial injuries died at the incidence site. In another study, 30% of those who could be transferred to the hospital died. This review aimed to revisit penetrating thoracic trauma with respect to complications and the strategies for airway management. While the risk of death in injuries with a sharp object is normally 1-8%, it reaches 25-28% when the cardiac box is included, and still, most of the patients are lost before they can come to the hospital. The consequences and management of penetrating thoracic trauma are mainly dependent on the extent of the injury to internal organs, as well as on the skill of the clinicians, airway obstruction, respiratory failure, and bleeding. Chest computed tomography (CT) is better than chest radiography in diagnosing the main bronchus or lobe/segment rupture. However, with the use of multi-channel multi-detector CT, the sensitivity of CT imaging has increased to 94% in the diagnosis of tracheobronchial injuries. While standard orotracheal intubation is sufficient in 75% of the patients, flexible bronchoscopy, intubation through the open wound or tracheostomy is required for airway provision in the rest. Clinical suspicion is the first diagnostic tool in a patient with penetrating airway trauma, and early treatment with multidisciplinary teamwork is life-saving.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; airway; thorax; trachea; trauma; trachea; thorax; trauma; airway.